Cambridge primary English Learner's book 2 - Budgell, Gill (United kingdom : Cambridge university press, 2021)
Cambridge Primary English Learner's Book 2 (Second Edition) is designed for young learners in the second year of primary education, continuing the development of their English language skills. This book focuses on further enhancing vocabulary, grammar, reading, writing, speaking, and listening abilities.
Keywords: English : Textbook